Health Systems in Transition : Canada - Gregory P. Marchildon (University of Toronto Press, 2013)
Canada is a high-income country with a population of 33 million people. Its economic performance has been solid despite the recession that began in 2008. Life expectancy in Canada continues to rise and is high compared with most OECD countries; however, infant and maternal mortality rates tend to be worse than in countries such as Australia, France and Sweden. About 70% of total health expenditure comes from the general tax revenues of the federal, provincial and territorial governments. Most public revenues for health are used to provide universal medicare (medically necessary hospital and physician services that are free at the point of service for residents) and to subsidise the costs of outpatient prescription drugs and long-term care. Health care costs continue to grow at a faster rate than the economy and government revenue, largely driven by spending on prescription drugs. In the last five years, however, growth rates in pharmaceutical spending have been matched by hospital spending and overtaken by physician spending, mainly due to increased provider remuneration.